EMPLOYEE EMPOWERMENT IN GLOBAL SCENARIO: AN EMPIRICLE STUDY - Sharma, Ms. Rajnil (IJRDO - Journal of Business Management, 2016)
Organizations are continuously upgrading their technology, processes, and systems to cope with competition, challenging environment and meeting customers demands. However they have failed to act upon the satisfaction of the employees, who are the internal customers of the firm. Can an organization service the needs of the customers properly when they fail to satisfy the needs of the internal customers? Organization’s success depends on employees’ performance. Creating a well-rounded approach for managing and coaching your work force requires the expertise of a human resources leader and the support of your company’s executive leadership. Employee, the key asset of every organization, is undoubtedly an indispensable factor determining the scope and success of any entity. No matter how capital intensive a company or industry may grow to be, one can’t but admit that certain roles and functionalities require human interference and no kind of technology can replace such human indulgence. In this era of globalisation there is need for employees’ empowerment in order to enable organisation to respond quickly to any changes in the macro- environment. Therefore, the aim of this paper was to find out what should be done in organisations to enhance employee empowerment. The outcome from the review indicates that employee empowerment is essential in this era of globalisation to enable the organisation to respond quickly to any changes in the environment and reduce employee turnover and increase job satisfaction among employees.